2013
DOI: 10.1371/journal.pgen.1003723
|View full text |Cite
|
Sign up to set email alerts
|

Deep Resequencing of GWAS Loci Identifies Rare Variants in CARD9, IL23R and RNF186 That Are Associated with Ulcerative Colitis

Abstract: Genome-wide association studies and follow-up meta-analyses in Crohn's disease (CD) and ulcerative colitis (UC) have recently identified 163 disease-associated loci that meet genome-wide significance for these two inflammatory bowel diseases (IBD). These discoveries have already had a tremendous impact on our understanding of the genetic architecture of these diseases and have directed functional studies that have revealed some of the biological functions that are important to IBD (e.g. autophagy). Nonetheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(150 citation statements)
references
References 43 publications
4
145
0
1
Order By: Relevance
“…This analysis was performed on total memory CD4 T cells, not myelin-specific T cells, suggesting that MS patients may inherently be more responsive to IL-23, which suggests that IL-23R may be a susceptibility factor. IL-23R polymorphism is associated with multiple autoimmune diseases (58)(59)(60), but it has not yet shown a significant correlation with MS risk. An alternative hypothesis is that the inflammatory process in MS may enhance IL-23R sensitivity and perhaps contribute to exacerbation rates or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was performed on total memory CD4 T cells, not myelin-specific T cells, suggesting that MS patients may inherently be more responsive to IL-23, which suggests that IL-23R may be a susceptibility factor. IL-23R polymorphism is associated with multiple autoimmune diseases (58)(59)(60), but it has not yet shown a significant correlation with MS risk. An alternative hypothesis is that the inflammatory process in MS may enhance IL-23R sensitivity and perhaps contribute to exacerbation rates or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The largest genome-wide association study to date in IBS contained only around 5,500 individuals [38], which compared with 30 to 40,000 in some inflammatory bowel disease cohorts [39, 40], limits the ability to draw firm conclusions.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Previous studies have revealed the significance of genetic variations in IBD pathogenesis by performing large genome-wide association studies (GWAS) 17 . However, the genetic variants that have been associated with UC and CD can only explain the 20-25% of all IBD cases, suggesting the presence of additional contributing factors 18 .…”
Section: Molecular Systems Approach In Ibdmentioning
confidence: 99%